ESCREVER NA UNIVERSIDADE - Figueriedo Brito, Robson (Sapere Aude, 2019)
VIEIRA, Francisco Eduardo; FARACO, Carlos Alberto. Escrever na universidade: fundamentos. v. 1. São Paulo: Parábola, 2019, 126 p.